Motivational model for continuous intention of electronic portfolio usage among students - Mobarhan, Rokhsareh (2016)
The implementation of the electronic portfolio (e-Portfolio) has increased in higher education, as it can serve students in new and creative ways. However, despite its advantages, students are not willing to continue the use of the e-Portfolio system. One of the reasons is the lack of motivation to spend the time and effort required to use the system. The aim of this study is to provide a better understanding of the motivational factors affecting students’ continuous intention regarding e-Portfolio usage by means of proposing a motivational model. The model is based on the synergy of four theories, namely, self-determination theory, use and gratification theory, unified theory of acceptance and use of technology, and Information Systems continuance model. A qualitative approach using face-to-face interviews was employed to confirm the factors identified in the literature and to explore potential factors that are not currently presented in the literature. Thereafter, a quantitative method using the survey technique was applied to collect data from students. The survey yielded 374 useable responses which were further analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique. This technique was used to validate the measurement items and to test the hypotheses and research model. The results indicate that students’ satisfaction is the most significant predictor of the students’ continuous intention to use the e-Portfolio system, followed by social influences, perceived usefulness, facilitating conditions, feedback, long-term consequences of use, and perceived enjoyment. The results also indicate that five categories of uses and gratification, including outcome, content, process, social and technology gratification, have an influence on the students’ continuous intention to use e-Portfolio. Based on the findings, this study provides some practical recommendations for higher education institutions to enhance the continued use of e- Portfolio among students and classifies based on the different roles of managers and administrators, academic advisors and lecturers, designers and developers, and students.